Does gender play a role in peace journalism practices? An analysis of the Armenian and Azerbaijani coverage of the 44 days Karabakh war - Di Mauro, Teresa (Univerzita Karlova, Fakulta sociálních věd, 2022)
This study explores peace journalism practices in the context of the 44 days Karabakh war and whether the reporter's gender matters in applying this approach. The research draws on analysis of eight conducted reconstruction interviews with Armenian and Azerbaijani female and male reporters. The results show that peace journalism faces several challenges in the region: from press freedom restrictions, to the prohibition of accessing the war zone especially for the Azerbajani reporters, to the fear of being targeted as traitors, and to the additional difficulties of those reporters who are refugees themselves. Furthemore, when applying gender lenses to the analysis, the impact of patriarchal norms in the reporters' work is evident. While women were more likely to access war victims, but faced challenges when embedded in the masculine environment of the army, men would be seen as 'weak' for adopting a more peaceful approach in their reporting. Although there is no shared view among the respondents on the role of the reporter's gender in appling peace journalism, the ingrained gender roles of the two societies help explain why female reporters are more likely than their male colleagues to embrace peace journalism. Keywords peace journalism, gender, gender roles, women reporters, patriarchy, women peace. Tato studie zkoumá praktiky mírové žurnalistiky v kontextu 44denní války v Karabachu a to, zda při uplatňování tohoto přístupu závisí na pohlaví novináře. Výzkum čerpá z analýzy osmi provedených rekonstrukčních rozhovorů s arménskými a ázerbájdžánskými reportéry a reportérkami. Výsledky ukazují, že mírová žurnalistika čelí v regionu několika výzvám: od omezování svobody tisku přes zákaz vstupu do válečné zóny, zejména pro ázerbájdžánské reportéry, až po strach z toho, že se stanou terčem zrádců, nebo po zvláštní potíže těch reportérů, kteří jsou sami uprchlíky. Navíc při aplikaci genderového úhlu pohledu na analýzu je zřejmý dopad patriarchálních norem v práci novinářů. Zatímco ženy měly s větší pravděpodobností ...